Analysis of the Relationship Between the School Principal's Visionary Leadership and Kindergarten Teachers' Performance - Erna Kusumawati (Journal of Innovation in Educational and Cultural Research, 2023)
One of the important factors that influence the quality of teacher performance in is the service provided in the form of school principal leadership. This study aims to analyze the influence of the principal's visionary leadership on the performance of kindergarten teachers. The approach is quantitative, with causal survey techniques and path analysis methods. The sample in this study is the same as the reachable population, namely 87 teachers, consisting of 19 Kindergartens in the Batu Ceper sub-district, Tangerang City. Data Collection Techniques used in this research using questionnaires or questionnaires. Data were analyzed by descriptive and inferential analysis, to test the data analysis require for normality, homogeneity, and ty, linearity regression using SPSS (Statistical Package for Social Science) version-24. Besides that, the Normality Test is also used with the Kolmogrv Smirnov Test technique. The homogeneities was carried out by ANOVA test. Hypothesis testing was carried out with the help of the Excel program computer and using SPSS (Statistical Package for Social Science) software version-24 Based on the research results, Visionary leadership has a direct positive effect on the performance of kindergarten teachers in Batu Ceper, Tangerang City. This is evidenced by the results of the t-test statistic test for Visionary leadership with the acquisition of a tcount of 2.826 with a significant value of 0.000 which is smaller than 0.05, and Î² = 0.161 it can be concluded that there is a positive and significant influence of visionary leadership on the performance of kindergarten teachers in the Batu Ceper sub-district, Tangerang.